2020
DOI: 10.1038/s41598-020-62883-2
|View full text |Cite
|
Sign up to set email alerts
|

Two-Level Protein Methylation Prediction using structure model-based features

Abstract: protein methylation plays a vital role in cell processing. Many novel methods try to predict methylation sites from protein sequence by sequence information or predicted structural information, but none of them use protein tertiary structure information in prediction. In particular, most of them do not build models for predicting methylation types (mono-, di-, tri-methylation). To address these problems, we propose a novel method, Met-predictor, to predict methylation sites and methylation types using a suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Using bioinformatic tools, we scanned preferred motif sequences to predict PRMT substrates in skeletal muscle [ 97 , 98 ]. Contrary to PRMT1 and PRMT5 which prefer arginine- and glycine-rich RGG/RG sequences, earlier work indicated that CARM1 targets arginine residues neighboring PGM motifs [ 1 , 5 , 99 , 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using bioinformatic tools, we scanned preferred motif sequences to predict PRMT substrates in skeletal muscle [ 97 , 98 ]. Contrary to PRMT1 and PRMT5 which prefer arginine- and glycine-rich RGG/RG sequences, earlier work indicated that CARM1 targets arginine residues neighboring PGM motifs [ 1 , 5 , 99 , 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Next, residue-residue contacts are predicted from the MSA by the deep learning-based algorithms TripletRes/ResTriplet 27 and ResPRE 28 (see the Supporting Information Text S1 for details). Meanwhile, LOMETS threading 35 is performed to search for the query protein sequence against the PDB database to align the query to template structures to extract continuous fragments. These fragments are finally assembled into the full length structures by a replica-exchange Monte Carlo (REMC) simulation under the guidance of a composite force field consisting of the deep learning-predicted contacts, template-derived distance restraints, and knowledge-based energy terms calculated based on statistics of PDB structures.…”
Section: Protein Structure Predictionmentioning
confidence: 99%
“…PTMs can occur at specific sites within the 3D structure of a protein, and therefore, the structural context of a site can be informative for predicting its likelihood of being modified [ 60 62 ]. Given recent breakthroughs in predicting functional and structural protein properties using raw protein sequences [ 63 – 65 ], we can infer that predicting Ubi-sites by shortening the number of amino acids in the windows could result in a lower amount of implicit structural features that ML methods could obtain during training, compared to longer window sizes.…”
Section: Human Ubi-site Benchmarkmentioning
confidence: 99%